A comprehensive systematic review of healthcare workers’ perceptions of risk from exposure to emerging acute respiratory infectious diseases and the perceived effectiveness of strategies used to facilitate healthy coping in acute hospital and community healthcare settings - Yiwen, K.; Hegney, Desley; Drury, Vicki (University of Adelaide, 2010)
Background: Emerging acute respiratory infectious diseases, such as Severe Acute Respiratory Syndrome (SARS) and the Avian Influenza A/H5N1 virus are contagious with high morbidity and mortality rates. Hence, health care workers, who are in close contact with affected patients, face many risks. There need to be a greater understanding of: individual HCWs’ risk perceptions; adopted risk-mitigating strategies; and factors influencing both. Objectives: This review aimed to establish the best evidence regarding health care worker’s risk perceptions and workplace strategies towards emerging acute respiratory infectious diseases in acute hospital and community healthcare settings; and to make recommendations for practice and future research. Inclusion criteria: Participants - Studies that included male and female health care workers practising in acute and community health care settings were considered. Types of intervention(s)/ Phenomena of interest - This review considered studies that investigated: health care workers’ risk perceptions; perceived meaning/effectiveness of the individual and workplace strategies implemented; and the factors influencing both. Types of outcomes - This review focused on factors affecting: health care worker’ risk perceptions; use of risk-mitigating strategies; and their perceived meaning and effectiveness. Types of studies - Both qualitative and quantitative study designs published in the English language were including in the study.Search strategy: Using a three-step search strategy, the following databases from 1997-2009 were accessed: CINAHL, PubMed, SCOPUS, ScienceDirect, Sociological Abstracts, PsycINFO, and Web of Science. Methodological quality: Two independent reviewers assessed each paper for methodological validity prior to inclusion in the review using standardised critical appraisal instruments from the Joanna Briggs Institute. Disagreements were resolved through discussion, or with a third reviewer. Data extraction: Information was extracted by two independent reviewers from each paper using the standardised data extraction tools from JBI. Data synthesis: The findings are presented in narrative form, as textual pooling and statistical pooling was not possible for the qualitative and quantitative papers respectively. Results: Ten quantitative studies and one qualitative study were included in the review. Findings indicated that although health care workers perceived personal and familial health risks and stigmatization from their exposure to emerging acute respiratory infectious diseases, the majority were accepting of these risks. Organizational implementation of infection control measures; avoidance of patients; and complying with personal protective equipment were identified as risk-mitigating strategies. Demographic, individual and organizational factors were found to influence their risk perceptions and their adoption of these strategies.Conclusions: There is a nebulous relationship between health care workers’ risk perceptions and how these perceptions affect their use of risk-mitigating strategies. Hence, future research needs to examine the nuances of this relationship, as well as the influencing factors involved. In this review, several key factors influencing health care workers’ risk perceptions and risk-mitigating strategies were identified and these may form the implications for new practice. Implications for practice: Institutions need to: empower health care workers through education and training; protect them with organizational safeguards; and offer incentives to encourage willingness to work, especially for those with high risk perceptions. Implications for research: Future research need to examine the: differences between HCWs’ intentions to care during SARS and influenza outbreaks; relationship between intentions to care and actual care provided; difference between their intentions to care/resign and acceptance of risks; factors influencing their intentions to care; and factors influencing compliance to infection control measures.